(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Plate grips that attach to the car windshield, in relation to their types and structures, are important in ensuring the functionality and safety of vehicles. These handles are mainly divided into three different types: monolithic, modular and special design handles. Monolithic handles, produced as a whole, hold the mirror firmly. Modular handrails, on the other hand, consist of several parts, allowing easy replacement and repair. Specially designed handlebars are usually designed for specific car models, taking into account the aerodynamic and aesthetic aspects. Constructively, grips are differentiated according to materials, strength, and application conditions. For example, some handles are made of metal or high-quality plastic, which increases their impact resistance. On the other hand, the aerodynamic design helps to reduce the air resistance of the mirrors.These differences allow automakers to choose grips to suit different conditions and needs, increasing the overall performance of the car and driver safety.